Running away from phonological ambiguity, we stumble upon our words: Laboratory induced slips show differences between highly and lowly defensive people - Thieffry, Lola; Olyff, Giulia; Pioda, Lea; Detandt, Sandrine; Bazan, Ariane (Frontiers in Human Neuroscience, 2023)
Freud proposed that slips of the tongue, including apparently simple ones, always have a sense and constitute « a half-success and a half-failure » compromise resulting from defensive mechanisms. 55 subjects participated in a French adaptation of the Spoonerisms of Laboratory Induced Predisposition or SLIP-technique (Motley & Baars, 1976a) including 32 ‘neutral’ and 32 taboo spoonerisms and measures of defensiveness. In accordance with a psychoanalytical and empirically supported distinction (Erdelyi, 2006), we considered two kinds of defenses: elaborative or primary process and inhibitory or secondary process defenses, which were operationalized with the GeoCat and Phonological-Nothing (PN) WordList respectively. The GeoCat is a validated measure of primary process mentation and the PN WordList was shown to measure the defensive avoidance of language ambiguity. Participants produced 37 slips, with no significant difference in the number of ‘neutral’ and taboo slips. The GeoCat and the N/PN parameters explained 30% of the variance in the production of parapraxes, confirming the defensive logics of slips. When dividing the population in lowly and highly defensive participants (with the Marlowe Crowne Social Desirability scale), primary process mentation appears as a baseline default defense, but only highly defensive participants mobilize an additional inhibitory secondary process type of defense. Taking into account the a priori difference between taboo and ‘neutral’ parapraxes, highly defensive participants made 2.7 times more taboo parapraxes than lowly defensive participants. However, if ‘neutral’ parapraxes in both subgroups followed the same logic as the total group of parapraxes (significant contribution of primary process mentation in lowly defensives and of primary and secondary process mentation in highly defensives), these measures had no contribution to explain the occurrence of taboo parapraxes. We propose that Motley et al.'s prearticulatory editor, ensuring the censorship over taboo parapraxes, is an external instance of inhibition, proximal to uttering, equivalent to the censorship between the systems Preconscious and Conscious in Freud’s metapsychology. By contrast, the defenses measured in this research are internal, intimate control systems, probing for the censorship between the systems Unconscious and Preconscious, this is, for repression. This study contributes to support a psychodynamic explanatory model for the production of parapraxes.